2016
DOI: 10.1021/acschembio.6b00981
|View full text |Cite
|
Sign up to set email alerts
|

A Rationally Designed, General Strategy for Membrane Orientation of Photoinduced Electron Transfer-Based Voltage-Sensitive Dyes

Abstract: Voltage imaging with fluorescent dyes offers promise for interrogating the complex roles of membrane potential in coordinating the activity of neurons in the brain. Yet, low sensitivity often limits the broad applicability of optical voltage indicators. In this paper, we use molecular dynamics (MD) simulations to guide the design of new, ultra-sensitive fluorescent voltage indicators that use photoinduced electron transfer (PeT) as a voltage-sensing switch. MD simulations predict an approximately 16% increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
86
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 52 publications
(88 citation statements)
references
References 40 publications
2
86
0
Order By: Relevance
“…Rapid synaptic integration may be facilitated by higher maturity of transplanted cells. Using voltage‐sensitive fluorescent dyes to monitor spiking activity—a hallmark of neuronal maturation—we observed that 80% of 3D‐generated neurons fired action potentials at D31 of differentiation in vitro (Figure S13, Supporting Information). Such functionally mature neurons may integrate with the host neuronal architecture faster, and lead to rapid alleviation of disease symptoms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid synaptic integration may be facilitated by higher maturity of transplanted cells. Using voltage‐sensitive fluorescent dyes to monitor spiking activity—a hallmark of neuronal maturation—we observed that 80% of 3D‐generated neurons fired action potentials at D31 of differentiation in vitro (Figure S13, Supporting Information). Such functionally mature neurons may integrate with the host neuronal architecture faster, and lead to rapid alleviation of disease symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Voltage‐Sensitive Dye‐Based Imaging : D31 H1 hESC‐derived mDA neurons generated in pNIPAAm‐PEG hydrogels and seeded on laminin‐coated coverslips were labeled with voltage‐sensitive dyes dsVF2.2(OMe).Cl (500 × 10 −9 m ), and images were acquired with a W‐Plan‐Apo 63×/1.0 objective (Zeiss) and OrcaFlash4.0 sCMOS camera (sCMOS, Hamamatsu) and analyzed as previously described …”
Section: Methodsmentioning
confidence: 99%
“…VoltageFluor dyes do both of these well, and bath application of VF dyes gives membrane localized fluorescence. 12, 14 However, small molecule voltage indicators display poor selectivity for particular cell types and stain all membranes, making cellular resolution difficult. 13, 16 We have developed photoactivation methods to address the problem of contrast, 17 and development of complementary approaches with genetically encoded components is underway in our lab.…”
Section: Universal Challenges For Voltage Imagingmentioning
confidence: 99%
“…5,[34][35][36] Therefore, we were eager to adapt phosphorous-substituted xanthenes into a fluorescent sensing scaffold. Previous work in our lab suggests that xanthene dyes with a range of bridgehead (O, 37 C, 27 Si 38 ) and terminal atoms (O 27, 37 or substituted N [38][39] can be employed as voltage-sensitive dyes via introduction of a lipophilic, conjugated molecular wire. We hypothesized that the installation of phenylenevinylene molecular wires into the context of a phosphorous-subsituted xanthene dye would yield voltage-sensitive indicators with emission and excitation maxima above 700 nm.…”
mentioning
confidence: 99%